2016
DOI: 10.1016/j.biochi.2015.11.024
|View full text |Cite
|
Sign up to set email alerts
|

Absorption and retention of free and milk protein-bound cyano- and hydroxocobalamins. An experimental study in rats

Abstract: Cbl added to milk (spiked with rbTC) has high bioavailability matching that of free Cbl. OHCbl and CNCbl are absorbed equally well, but much more OHCbl accumulated in the liver. Benefits of oral supplementation with OHCbl compared to CNCbl should be investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
29
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 31 publications
11
29
0
Order By: Relevance
“…The rational is that this form of the vitamin is both chemically stable and cheap. In agreement with the previous studies [11][12][13][14], we find that CN-B12 induces a higher increase in the circulating total Cbl in comparison to HO-B12. Interestingly, administration of HO-B12 is as efficient-if not slightly better-in improving other markers of an impaired B12 status, notably MMA.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The rational is that this form of the vitamin is both chemically stable and cheap. In agreement with the previous studies [11][12][13][14], we find that CN-B12 induces a higher increase in the circulating total Cbl in comparison to HO-B12. Interestingly, administration of HO-B12 is as efficient-if not slightly better-in improving other markers of an impaired B12 status, notably MMA.…”
Section: Discussionsupporting
confidence: 93%
“…Several studies have documented that both forms are retained alike after oral uptake [9][10][11], but the tissue distributions of the two absorbed vitamins differ. For example, in rats, considerably more B12 is internalized in the liver after ingestion of HO-B12, when compared to an equal dose of CN-B12 [12,13]. Conversely, the circulating level of B12 is much higher upon administration of CN-B12 than after intake of similar dose of HO-B12 [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both human and animal studies have demonstrated that synthetic and natural forms of B 12 are absorbed equally (7)(8)(9)(10)(11) . However, our recent data show that HO-B 12 accumulates in the liver to a higher degree than CN-B 12 , but that the patterns are opposite in the brain and plasma.…”
mentioning
confidence: 99%
“…Here, ADO-B 12 acts as a cofactor for methylmalonyl-CoA mutase in the conversion of methylmalonyl-CoA to succinyl-CoA in the mitochondria. CH 3 -B 12 acts as a cofactor for methionine synthase in the folatedependent methylation of homocysteine to methionine in the cytoplasm (1,2) .Both human and animal studies have demonstrated that synthetic and natural forms of B 12 are absorbed equally (7)(8)(9)(10)(11) . However, our recent data show that HO-B 12 accumulates in the liver to a higher degree than CN-B 12 , but that the patterns are opposite in the brain and plasma.…”
mentioning
confidence: 99%